Dengue, Zika e Chikungunya: análise dos efeitos de campanhas preventivas e uma abordagem da aprendizagem significativa em Instituição de Ensino Federal - Cavalcanti, Anne Caroline Simões (Brasil, 2023)
Dengue, Zika and Chikungunya are viral diseases that afect millions of people of the entire world. They are transmitted by the female gender of the moskito Aedes aegypti and today, they are presente in all brazilian territory. The Ministry of Health and Ministry of Education created a program called School Health, which approaches about ways of prevention for these diseases and the promotion of health. It’s school’s and teacher’s responsibility, as health promoters, to spread the knowledge about the vector, its characteristics and etiological agents. In this research, we verified the effects of prevention campaigns and awareness in students of a federal institution, evaluating the researched population knowledge about the vector and its etiological agents, comparing the level of knowledge of the different educational levels. Coming from the idea that health education is liked to the meaningful learning, the tool for this research was a semi-open quiz, which application was done in two steps: 1) The quiz was applied to check the students previous knowledge. 2) The quiz was applied after classes with exhibition of a biology didactic video about the vector and its diseases social-political-economical implications using a PowerPoint® presentation with recent and contextualized information about these arboviruses. As result of the first avaliation, we noticed that campaigns that are external of the schools environment had better impact in every researched class. We verified a difference between classes from the graduation level and high school level, with a better development in the first ones. Its suggested that more intense activities about diseases prevention can be done inside of the institution and more attention to be given to the contents related to this theme in courses of teachers formation willing that the promotion of health be na activity independent of the promotional campaigns only done during the epidemics.